Pelaksanaan Pemenuhan Jaminan Sosial Ketenagakerjaan Bagi Juru Parkir Resmi di Kabupaten Banyumas - Krisna Praditya Saputra; Susilo Wardani; Selamat Widodo (Kosmik Hukum, 2019)
National Development in implementing social security is carried out in the framework of complete human development and to create a society that is prosperous, just, prosperous, and equitable, both physically and spiritually based on Pancasila and the 1945 Constitution. This is regulated in Article 28H paragraph (3) which states that: "Every person has the right to social security which enables his complete development as a dignified human being." All workers should receive protection, both formal and informal, in this case, official parking attendants work for a living which is very vulnerable to the risk of work accidents. This research discusses how the implementation of the fulfillment of labor social security rights for official parking attendants in the Banyumas Regency and what are the obstacles in the fulfillment of the employment social security rights for official parking attendants in Banyumas Regency. The method used in this research, namely the normative juridical method, is carried out through a literature study which examines mainly secondary data in the form of laws and regulations, agreements/contracts, or other legal documents, as well as research results, assessment results, and other references. As for the implementation of the fulfillment of labor social security rights for official parking attendants in Banyumas Regency, namely the parking attendants' obligations to follow the BPJS Ketenagakerjaan so that social security is fulfilled for official parking attendants covered by the Transportation Agency. And what is an obstacle in the fulfillment of the employment social security rights for official parking attendants in Banyumas Regency is the low level of education which affects the level of awareness of workers in paying BPJS contributions, even though the Banyumas Regency Transportation Office requires every worker to participate in the social security program.Keywords: Labor Social Security, Parking Attendants, Department of Transportation